Impact of chronic systolic heart failure on lung structure–function relationships in large airways. Issue 13 (14th July 2016) - Chase, Steven C.; Wheatley, Courtney M.; Olson, Lyle J.; Beck, Kenneth C.; Wentz, Robert J.; Snyder, Eric M.; Taylor, Bryan J.; Johnson, Bruce D.
Abstract: Heart failure (HF) is often associated with pulmonary congestion, reduced lung function, abnormal gas exchange, and dyspnea. We tested whether pulmonary congestion is associated with expanded vascular beds or an actual increase in extravascular lung water (EVLW) and how airway caliber is affected in stable HF. Subsequently we assessed the influence of an inhaled short acting beta agonist (SABA). Thirty‐one HF (7F; age, 62 ± 11 years; ht. 175 ± 9 cm; wt. 91 ± 17 kg; LVEF, 28 ± 15%) and 29 controls (11F; age; 56 ± 11 years; ht. 174 ± 8 cm; wt. 77 ± 14 kg) completed the study. Subjects performed PFTs and a chest computed tomography (CT) scan before and after SABA. CT measures of attenuation, skew, and kurtosis were obtained from areas of lung tissue to assess EVLW. Airway luminal areas and wall thicknesses were also measured. CT tissue density suggested increased EVLW in HF without differences in the ratio of airway wall thickness to luminal area or luminal area to TLC (skew: 2.85 ± 1.08 vs. 2.11 ± 0.79, P < 0.01; Kurtosis: 15.5 ± 9.5 vs. 9.3 ± 5.5 P < 0.01; control vs. HF). PFTs were decreased in HF at baseline (% predicted FVC:101 ± 15% vs. 83 ± 18%, P < 0.01;FEV1:103 ± 15% vs. 82 ± 19%, P < 0.01;FEF25–75: 118 ± 36% vs. 86 ± 36%, P < 0.01; control vs. HF). Airway luminal areas, but not CT measures, were correlated with PFTs at baseline. The SABA cleared EVLW and decreased airway wall thickness but did not change luminal area. Patients with HF had evidence of increased EVLW, but not an expanded bronchial circulation. Airway caliber was maintained relative to controls, despite reductions in lung volume and flow rates. SABA improved lung function, primarily by reducing EVLW. Abstract : Heart failure is associated with pulmonary congestion and reduced lung function. We assessed airway structure–function relationships using CT imaging. Heart failure patients maintain their large airway structure despite reductions in lung volumes and flows.